Non-proteinogenic amino acids mitigate oxidative stress and enhance the resistance of common bean plants against Sclerotinia sclerotiorum - Nehela, Yasser; Mazrou, Yasser S. A.; El_Gammal, Nehad A.; Atallah, Osama; Xuan, Tran Dang; Elzaawely, Abdelnaser A.; El-Zahaby, Hassan M.; Abdelrhim, Abdelrazek S.; Behiry, Said I.; Hafez, Emad M.; Makhlouf, Abeer H.; Hussain, Warda A. M. (Frontiers in Plant Science, 2024)
White mold, caused by the necrotrophic fungus Sclerotinia sclerotiorum, is a challenging disease to common bean cultivation worldwide. In the current study, two non-proteinogenic amino acids (NPAAs), γ-aminobutyric acid (GABA) and ß-alanine, were suggested as innovative environmentally acceptable alternatives for more sustainable management of white mold disease. In vitro, GABA and ß-alanine individually demonstrated potent dose-dependent fungistatic activity and effectively impeded the radial growth and development of S. sclerotiorum mycelium. Moreover, the application of GABA or ß-alanine as a seed treatment followed by three root drench applications efficiently decreased the disease severity, stimulated plant growth, and boosted the content of photosynthetic pigments of treated S. sclerotiorum-infected plants. Furthermore, although higher levels of hydrogen peroxide (H2O2), superoxide anion (O2 •-), and malondialdehyde (MDA) indicated that S. sclerotiorum infection had markedly triggered oxidative stress in infected bean plants, the exogenous application of both NPAAs significantly reduced the levels of the three studied oxidative stress indicators.Additionally, the application of GABA and ß-alanine increased the levels of both non-enzymatic (total soluble phenolics and flavonoids), as well as enzymatic (catalase [CAT], peroxidases [POX], and polyphenol oxidase [PPO]) antioxidants in the leaves of S. sclerotiorum-infected plants and improved their scavenging activity and antioxidant efficiency. Applications of GABA and ß-alanine also raised the proline and total amino acid content of infected bean plants. Lastly, the application of both NPAAs upregulated the three antioxidant-related genes PvCAT1, PvCuZnSOD1, and PvGR. Collectively, the fungistatic activity of NPAAs, coupled with their ability to alleviate oxidative stress, enhance antioxidant defenses, and stimulate plant growth, establishes them as promising eco-friendly alternatives for white mold disease management for sustainable bean production.